Sensitivity of Arctic ozone loss to stratospheric H2O - Feck, T.; Grooß, J.-U.; Riese, M. (Geophysical Research Letters, 2008)
Likely causes of a future increase in stratospheric H2O are a rise in tropospheric CH4 and H-2 leakages from an increased integration of hydrogen into the energy supply system. Here we evaluate the impact of potential future stratospheric H2O increases on Arctic ozone loss by comparing ozone loss proxies based on two different mechanisms of chlorine activation. In particular, the H2O dependence of the volume of air is analyzed where temperatures are low enough to form nitric acid trihydrate, denoted as V-PSC, and for C1 activation on liquid sulfate aerosols, denoted as V-AC1. We show that V-AC1 increases faster than VPSC with increasing H2O mixing ratios in the altitude range of 400 K to 550 K potential temperature. As a consequence, the additional ozone column loss is expected to be most pronounced for cold winters and large H2O increases and to be significantly higher when V-AC1 is used as a proxy.